Technical specifications of qualified sportswomen who specialize in race walking for 10 km - S.P. Sovenko; H.B. Budkevych; T.V. Lytvynchuk (Physical Education of Students, 2014)
Purpose: to identify the main biomechanical characteristics of qualified athletes. Material : The study involved nine athletes. Video footage used for hardware-software complex LUMAX (number of dimensions - 891). Results : systematized data on more than 15 references. Biomechanical characteristics of vehicles covered nine best athletes in the championship of Ukraine 2013. A comparative analysis of the results with the scientific and methodological literature. Notes the importance of calculating the utilization of anthropometric data (ratio of stride length and growth athlete). Conclusions : The main priority for enhancing athletic performance Ukrainian athletes is an increase of 2-3 cm length of stride, with increasing frequency index steps to 3.45 steps per second.